Mempertimbangkan Kembali Pemikiran Gus Dur Bagi Kontekstualisasi Ajaran Islam di Indonesia - Damanhuri - (Millah: Journal of Religious Studies, 2003)
"Pribumisasi Islam" is a term used by Abdurrahman Wahid (Gus Dur) for  contextualisation of Islamic doctrine in Indonesia. It's also equally used as  counter of discourse of "Arabization" (Arabic oriented) of religiousity that  tends to formalize of religion and lacks of it's progressivity. In order to the  grasp deep meaning of the doctrine, therefore, Gus Dur develops new models  of interpretation based on cultural that will r-glue to roots of tradition. So universality values of Islam, then, fuse with locality values. This unity make a  tranformative combination of understanding contextuality of doctrine.